Government of Tripura Draft Annual Plan (2008-2009) and 11th Five Year Plan (2007-12) Part - I (Summary) - Planning Commission (Planning Commission, 2008)
The above vital rates indicate a better quality of life in Tripura despite several constraints and its backwardness. This is because of rising literacy rate as a result of wide spread free school education and mass literacy campaign through direct involvement of the people in the local decision-making process through the Panchayat/ Panchayat Samiti/Zilla Parishad. Over and above, effective coverage of health and family welfare services in the state is another responsible factor for attaining better quality of life.
Planning (P and C) Department Government of Tripura
Planning (P and C) Department Government of Tripura